Uruk, Irak: Forschungen im Rahmen der Interpretation und Publikation der Grundlagendaten - van Ess, Margarete (e-Forschungsberichte des DAI, 2023)
Since 2003, fieldwork in Uruk-Warka, Southern Iraq had to be substituted by intensive work on the final publications of previous excavation results. In recent years, these results were processed for secondary interpretation and presentation to the public. 3D reconstructions of architecture excavated in Uruk as well as animations of 3D data and interpretations derived from analysis of all archaeological and additional philological sources. These were combined and designed for an exhibition and merged for future scientific research. Furthermore, a project presenting additional analyses of 14C samples from the late Uruk and the Jemdet Nasr periods has been carried out and published.